Acceleration of the G1/S phase transition by expression of cyclins D1 and E with an inducible system. - Resnitzky, D (1994)
Conditional overexpression of human cyclins B1, D1, and E was accomplished by using a synthetic cDNA expression system based on the Escherichia coli tetracycline repressor. After induction of these cyclins in asynchronous Rat-1 fibroblasts, a decrease in the length of the G1 interval was observed for cyclins D1 and E, consistent with an acceleration of the G1/S phase transition. We observed, in addition, a compensatory lengthening of S phase and G2 so that the mean cell cycle length in populations constitutively expressing these cyclins was unchanged relative to those of their uninduced counterparts. We found that expression of cyclin B1 had no effect on cell cycle dynamics, despite elevated levels of cyclin B-associated histone H1 kinase activity. Induction of cyclins D1 and E also accelerated entry into S phase for synchronized cultures emerging from quiescence. However, whereas cyclin E exerted a greater effect than cyclin D1 in asynchronous cycling cells, cyclin D1 conferred a greater effect upon stimulation from quiescence, suggesting a specific role for cyclin D1 in the G0-to-G1 transition. Overexpression of cyclins did not prevent cells from entering into quiescence upon serum starvation, although a slight delay in attainment of quiescence was observed for cells expressing either cyclin D1 or cyclin E. These results suggest that cyclins D1 and E are rate-limiting activators of the G1-to-S phase transition and that cyclin D1 might play a specialized role in facilitating emergence from quiescence.